Amifostine (WR-2721) Mitigates Cognitive Injury Induced by Heavy Ion Radiation in Male Mice and Alters Behavior and Brain Connectivity - Boutros, Sydney Weber; Zimmerman, Benjamin; Nagy, Sydney C.; Lee, Joanne S.; Perez, Ruby; Raber, Jacob (Frontiers in Physiology, 2021)
The deep space environment contains many risks to astronauts during space missions, such as galactic cosmic rays (GCRs) comprised of naturally occurring heavy ions. Heavy ion radiation is increasingly being used in cancer therapy, including novel regimens involving carbon therapy. Previous investigations involving simulated space radiation have indicated a host of detrimental cognitive and behavioral effects. Therefore, there is an increasing need to counteract these deleterious effects of heavy ion radiation. Here, we assessed the ability of amifostine to mitigate cognitive injury induced by simulated GCRs in C57Bl/6J male and female mice. Six-month-old mice received an intraperitoneal injection of saline, 107 mg/kg, or 214 mg/kg of amifostine 1 h prior to exposure to a simplified five-ion radiation (protons, 28Si, 4He, 16O, and 56Fe) at 500 mGy or sham radiation. Mice were behaviorally tested 2–3 months later. Male mice that received saline and radiation exposure failed to show novel object recognition, which was reversed by both doses of amifostine. Conversely, female mice that received saline and radiation exposure displayed intact object recognition, but those that received amifostine prior to radiation did not. Amifostine and radiation also had distinct effects on males and females in the open field, with amifostine affecting distance moved over time in both sexes, and radiation affecting time spent in the center in females only. Whole-brain analysis of cFos immunoreactivity in male mice indicated that amifostine and radiation altered regional connectivity in areas involved in novel object recognition. These data support that amifostine has potential as a countermeasure against cognitive injury following proton and heavy ion irradiation in males.